BORDER CROSSING AND MEXICAN-AMERICAN IDENTITY IN THE CIRCUIT - Anggi Puspitasari (Mahakarya: Jurnal Mahasiswa Ilmu Budaya, 2024)
As a land of immigrants, America is expected to provide an environment free of discrimination. However, many literary works highlight the struggles faced by Mexican immigrants, including The Circuit by Francisco Jiménez, which depicts the challenges experienced by Mexican-American families. This study uses a descriptive qualitative research design to examine the Mexican-American identity after crossing the border through Gloria Anzaldúa's (1987) Borderlands theory. The data in this study are in the form of sentences. The data was taken from The Circuit as the primary data source. The findings reveal Panchito's hybrid identity, negotiated between his Mexican heritage and the realities of life in America. Despite facing language barriers and discrimination challenges, Panchito maintains a connection to his cultural roots. This study offers a new perspective on identity negotiations in the borderlands by using The Circuit as a primary data source, which contributes to a deeper understanding of the Mexican-American immigrant experience